2017
DOI: 10.1002/2017gl073623
|View full text |Cite
|
Sign up to set email alerts
|

Albedo changes after fire as an explanation of fire‐induced rainfall suppression

Abstract: Observational evidence of rainfall suppression by fire has recently been documented in African drylands, but the underlying mechanism remains poorly understood. Here we investigate the extent to which fire‐induced changes in latent heat flux and albedo may inhibit boundary layer predisposition to convective rainfall. We use Modern‐Era Retrospective analysis for Research and Applications, Version 2 reanalysis data from the Kalahari region of Southern Africa to drive a low‐dimensional boundary layer growth model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…They also affect other fluxes and pools, like the reduction of aboveground litter due to fire. But they are also needed when running in coupled mode within the Earth System Model CNRM‐ESM as DOC is one of the main inputs of C to the global ocean (Resplandy et al, 2018) and fires and LCC also affect the physical climate (see for instance Saha, D'Odoricco, & Scanlon, 2017 for fire and De Noblet‐Ducoudré et al, 2012 or Lawrence & Chase, 2010 for LCC).…”
Section: Discussionmentioning
confidence: 99%
“…They also affect other fluxes and pools, like the reduction of aboveground litter due to fire. But they are also needed when running in coupled mode within the Earth System Model CNRM‐ESM as DOC is one of the main inputs of C to the global ocean (Resplandy et al, 2018) and fires and LCC also affect the physical climate (see for instance Saha, D'Odoricco, & Scanlon, 2017 for fire and De Noblet‐Ducoudré et al, 2012 or Lawrence & Chase, 2010 for LCC).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies across the Amazon have focused on deforestation patches in the heavily deforested southern Amazon, where the analysis is complicated by biomass-burning aerosol associated with deforestation and the coincidence of meteorological and land-cover gradients (80). Over the Sahel, negative correlations between dry season fires and following wet season rainfall suggest reduced rain over devegetated regions (81), potentially driven by increased albedo (82).…”
Section: Local Scale (One Kilometer To Hundreds Of Kilometers)mentioning
confidence: 99%
“…Such a significant CO 2 source needs to be considered in the current studies of environment and model simulation. Previous study (Saha et al, ) also found that the fire can increase albedo and latent heat, which leads to less convective precipitation. As suggested in Saha et al (), the brightening after fire as a result of drier soils and losing senescent vegetation is responsible for rainfall suppression.…”
Section: Resultsmentioning
confidence: 77%
“…Previous study (Saha et al, ) also found that the fire can increase albedo and latent heat, which leads to less convective precipitation. As suggested in Saha et al (), the brightening after fire as a result of drier soils and losing senescent vegetation is responsible for rainfall suppression. It will further lead to more severe droughts and wildfires in California in the future, which will release more CO 2 to the atmosphere.…”
Section: Resultsmentioning
confidence: 77%